2013
DOI: 10.1021/ja400761x
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+ Binds to the Surface of Thymidylate Synthase and Affects Hydride Transfer at the Interior Active Site

Abstract: Thymidylate synthase (TSase) produces the sole intracellular de novo source of thymidine (i.e. the DNA base T) and thus is a common target for antibiotic and anticancer drugs. Mg2+ has been reported to affect TSase activity, but the mechanism of this interaction has not been investigated. Here we show that Mg2+ binds to the surface of Escherichia coli TSase and affects the kinetics of hydride transfer at the interior active site (16 Å away). Examination of the crystal structures identifies a Mg2+ near the glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 80 publications
3
42
1
Order By: Relevance
“…We have recently studied the ion’s mechanism of action through comprehensive kinetic, structural, and dynamics analyses [72]. Fluorescence assays, crystal structures, and NMR chemical shift changes show that Mg 2+ loosely binds (K d =3.7 mM) to the surface of TSase and forms a bridge between the glutamyl moiety of the folate cofactor and the enzyme through an H-bonding network.…”
Section: Folate In Thymidylate Synthasementioning
confidence: 99%
See 1 more Smart Citation
“…We have recently studied the ion’s mechanism of action through comprehensive kinetic, structural, and dynamics analyses [72]. Fluorescence assays, crystal structures, and NMR chemical shift changes show that Mg 2+ loosely binds (K d =3.7 mM) to the surface of TSase and forms a bridge between the glutamyl moiety of the folate cofactor and the enzyme through an H-bonding network.…”
Section: Folate In Thymidylate Synthasementioning
confidence: 99%
“…(C) Change in chemical shift of each residue shown from white (no change) to red (maximum change). Reproduced from ref [72] with permission from ACS.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, both our experiments and computations suggest TSase exploits concerted protein motions in catalyzing chemical transformations. [65][66][67][68] Particularly, our experiments with Y209W ecTSase demonstrated that protein motions at various time calculations. 23,108,[130][131][132] Compared with the extensively studied "model protein" DHFR, most enzymes are more similar to TSase, which have more rigid structures and sophisticated mechanisms.…”
Section: Chapter VII Summary Impact and Future Directionsmentioning
confidence: 69%
“…65 Chapter IV extends this methodology to investigate the effects of Mg 2+ on the catalytic mechanism of TSase, which complements the studies in Chapter III and highlights the importance of long-range interactions in TSase-catalyzed reaction. 66 Chapter V presents our QM/MM calculations on the proton transfer step and compares the results with the previously calculated hydride transfer step, providing molecular details underlying the experimental KIE results. 67 It is noteworthy that our computational results not only illustrate functionalities of specific protein residues that reconcile many previous experimental observations, but also provide new insights into the catalytic mechanism that can be examined by future experiments.…”
Section: "Case Study": Thymidylate Synthasementioning
confidence: 99%
See 1 more Smart Citation